2004
DOI: 10.1111/j.1476-5810.2004.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of canine mast cell tumours with prednisolone and radiotherapy

Abstract: This retrospective study describes 35 dogs with non-resectable, grade I-III mast cell tumours on the head or limb treated with prednisolone (40 mg m(-2) daily) for 10-14 days prior to radiotherapy (4 x 800 cGy fractions at 7-day intervals) from a 4 MV linear accelerator. Prednisolone was continued at a reduced dose rate (20 mg m(-2)) during radiotherapy and for 2 months or longer afterwards. Eighteen of 24 tumours (75%) decreased in size in response to prednisolone treatment. By 6-8 weeks following radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 16 publications
1
63
1
4
Order By: Relevance
“…The purpose of this study was to assess the response to a previously unpublished chemotherapy protocol for gross MCT in dogs for whom surgery and/or radiotherapy were not suitable using two agents that have shown efficacy against round cell tumours. Prednisolone is widely used in chemotherapy regimens for canine MCTs (McCaw and others 1994, Thamm and others 1999, 2006, Davies and others 2004) and has been shown to inhibit mast cell proliferation in vitro (Takahashi and others 1997); it has also been shown to cause a reduction of size of gross MCTs before radiotherapy (Dobson and others 2004) or surgery (Stanclift and Gilson 2008). Chlorambucil is an alkylating agent that has therapeutic indications in canine round cell tumours, including MCT, lymphoma, chronic lymphoid leukaemia and some myelomas (Carberry and others 1987, Chun and others 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study was to assess the response to a previously unpublished chemotherapy protocol for gross MCT in dogs for whom surgery and/or radiotherapy were not suitable using two agents that have shown efficacy against round cell tumours. Prednisolone is widely used in chemotherapy regimens for canine MCTs (McCaw and others 1994, Thamm and others 1999, 2006, Davies and others 2004) and has been shown to inhibit mast cell proliferation in vitro (Takahashi and others 1997); it has also been shown to cause a reduction of size of gross MCTs before radiotherapy (Dobson and others 2004) or surgery (Stanclift and Gilson 2008). Chlorambucil is an alkylating agent that has therapeutic indications in canine round cell tumours, including MCT, lymphoma, chronic lymphoid leukaemia and some myelomas (Carberry and others 1987, Chun and others 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported the use of prednisolone in a neoadjuvant setting to reduce MCT mass before radiotherapy (Dobson and others 2004) and, more recently, before surgery (Stanclift and Gilson 2008). Interestingly, both these studies reported short‐term response rates of measurable tumours to be in the order of 70 to 75 per cent; however, as the tumours were either surgically removed within seven to 35 days (mean nine days) or irradiated after 10 to 14 days, these short‐term responses are not directly comparable with the present or previous studies where response rates have been reported according to WHO criteria, which require the response to be maintained for four weeks (WHO 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is well known that the complete removal of the tumor is the goal, but also additional treatment, such as radiotherapy or chemotherapy, may be necessary [45,73].…”
Section: Treatment Of Human Mastocytosis and Cmctsmentioning
confidence: 99%
“…Observase uma reposta de cerca de 20% quando utilizada como agente único, e de curta duração (McCAW et al, 1994;VAIL, 1999;DOBSON et al, 2004;HAYES et al, 2007;STANCLIFT;GILSON, 2008). Takahashi et al (1997) descreveram a ação dos corticosteroides como inibidores da proliferação celular nos mastocitomas caninos e indutores de apoptose das células neoplásicas in vitro.…”
Section: Fatores Prognósticosunclassified
“…A localização do tumor é relatada por alguns autores como um fator prognóstico. Mastocitomas em leito ungueal, cavidade oral, nariz, regiões mucocutâneas, região inguinal, prepúcio e períneo estariam associados à um pior prognóstico em comparação aqueles localizados em outras regiões do corpo (AL-SARRAF et al, 1996;BAKER-GABB;FRANCE, 2003;GIEGER et al, 2003;VAIL, 2007;WELLE et al, 2008 , 1984;BAKER-GABB;FRANCE, 2003;DOBSON et al, 2004;KIUPEL et al, 2004;SPUGNINI et al, 2006;BROCKS et al, 2008;TAKEUCHI et al, 2013 (ABBADIE et al, 1999;SCASE et al, 2006;ROMANSKI et al, 2007;WEBSTER et al, 2007;ELSTON et al, 2009;VASCELLARI et al, 2013 (PEREIRA et al, 2002;PATSIKAS et al, 2006;PEREIRA et al, 2008 De forma geral, diversos autores sugerem que pacientes com mastocitoma de qualquer grau e que tenham envolvimento de linfonodo regional, possuem um risco maior de óbito decorrente da doença (TURREL et al, 1988;GERRITSEN et al, 1998;VAIL, 1999;VAIL, 2003).…”
Section: Intervalo Livre De Doença (%)unclassified